Derivatization of estrogens enhances specificity and sensitivity of analysis of human plasma and serum by liquid chromatography tandem mass spectrometry - Faqehi, Abdullah M.M.; Cobice, Diego F.; Naredo, Gregorio; Mak, Tracy C.S.; Upreti, Rita; Gibb, Fraser W.; Beckett, Geoffrey J.; Walker, Brian R.; Homer, Natalie Z.M.; Andrew, Ruth (Talanta (Oxford), 2016)
Estrogens circulate at concentrations less than 20pg/mL in men and postmenopausal women, presenting analytical challenges. Quantitation by immunoassay is unreliable at these low concentrations. Liquid chromatography tandem mass spectrometry (LC–MS/MS) offers greater specificity and sometimes greater sensitivity, but ionization of estrogens is inefficient. Introduction of charged moieties may enhance ionization, but many such derivatives of estrogens generate non-specific product ions originating from the “reagent” group. Therefore an approach generating derivatives with product ions specific to individual estrogens was sought. Estrogens were extracted from human plasma and serum using solid phase extraction and derivatized using 2-fluoro-1-methylpyridinium-p-toluenesulfonate (FMP-TS). Electrospray in positive mode with multiple reaction monitoring using a QTrap 5500 mass spectrometer was used to quantify “FMP” derivatives of estrogens, following LC separation. Transitions for the FMP derivatives of estrone (E1) and estradiol (E2) were compound specific (m/z 362→238 and m/z 364→128, respectively). The limits of detection and quantitation were 0.2pg on-column and the method was linear from 1–400pg/sample. Measures of intra- and inter-assay variability, precision and accuracy were acceptable (<20%). The derivatives were stable over 24h at 10°C (7–9% degradation). Using this approach, E1 and E2, respectively were detected in human plasma and serum: pre-menopausal female serum (0.5mL) 135–473, 193–722pmol/L; male plasma (1mL) 25–111, 60–180pmol/L and post-menopausal female plasma (2mL), 22–78, 29–50pmol/L. Thus FMP derivatization, in conjunction with LC–MS/MS, is suitable for quantitative analysis of estrogens in low abundance in plasma and serum, offering advantages in specificity over immunoassay and existing MS techniques. [Display omitted] •Quantitative analysis of low amounts of estrone and estradiol in plasma and serum.•Quantitation across physiological range in men and pre- and post-menopausal women.•Methylpyridinium ether derivatives improve analytical specificity and sensitivity.